The Influence Of Behavior Through Safety Culture On Seafarers’ Performance On Merchant Ship - Mudiyanto Mudiyanto; Elva Febriana Anggraeny; Faishal Rabani Pribadi Putra (Kapal: Jurnal Ilmu Pengetahuan dan Teknologi Kelautan, 2026)
The aim of this study is to analyze the behavior of ship crews in implementing a safety culture towards performance on merchant ships..This study uses a quantitative approach to analyze the influence of behavior through safety culture on seafarers' performance on merchant ships. The sample used in this study consisted of 100 respondents, selected using a sampling technique using simple random sampling. The data was collected, the analysis was carried out using SmartPLS software to analyze complex structural models, including measuring the causal relationship between variables.The findings in this studySafety culture as a mediator has a significant influence on the relationship between behavioral variables and seafarer performance, namely by translating behavior into safety actions.This study contributes by revealing that consistent implementation of safety culture can form positive behaviors that significantly improve seafarers' operational performance and reduce the risk of accidents in the maritime sector. This study is different from previous studies that analyzed safety culture in the organizational sector, but this study analyzes safety culture on seafarers' performance in the maritime sector. The practical implications of this study are that shipping companies and port authorities need to strengthen safety culture through continuous training and implementation of regulations so that they can improve seafarers' performance and reduce accidents at sea.